2021
DOI: 10.51544/jalm.v6i2.2066
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Waktu Penyimpanan Darah Terhadap Kadar Hemoglobin Pada Komponen Whole Blood Darah Donor

Abstract: Blood transfusion is the process of distributing blood from donors to patients with the aim of replacing blood lost due to bleeding, surgery, shock and malfunctioning of the blood-forming organs that require replacement blood in the form of whole blood or blood components. Blood is stored with the First in First Out (FIFO) system, which is a system that regulates the expulsion of blood in which the first blood that enters will be removed first. The storage period of blood will experience changes in blood compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The dynamics of hemoglobin levels during the storage period could be influenced by erythrocyte damage. Saputro and Lestari (2021) reported that stored blood samples could increase hemoglobin levels. The longer the stored blood sample, the more erythrocytes can swell due to stiffness and loss of lipids in the cell membrane.…”
Section: Hemoglobin Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamics of hemoglobin levels during the storage period could be influenced by erythrocyte damage. Saputro and Lestari (2021) reported that stored blood samples could increase hemoglobin levels. The longer the stored blood sample, the more erythrocytes can swell due to stiffness and loss of lipids in the cell membrane.…”
Section: Hemoglobin Concentrationmentioning
confidence: 99%
“…This study found hypochromasia in blood samples stored for 6 to 48 hours, with a score of 4+. Saputro and Lestari (2021) reported that the longer blood samples are stored, the more hemoglobin in the erythrocytes will be released into the blood plasma, so that the hemoglobin level in the erythrocytes decreases and can cause hypochromasia in the erythrocytes.…”
Section: Morphology Of Erythrocytementioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, storage at temperatures above 6°C causes the growth of bacteria very quickly so that blood transfusions can be fatal for the recipient of the blood [3]. The temperature limit of 2°C is also very important because red blood cells are very sensitive to clotting, where if the red blood cells freeze, the blood cell walls will burst and the hemoglobin will come out (hemolysis) [4] [5]. Therefore, blood banks need to ensure the quality of blood so that there is no risk of damage during storage.…”
Section: Introductionmentioning
confidence: 99%